1993
DOI: 10.1093/tropej/39.6.365
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology of Acute Diarrhoea in Hospitalized Children in Rio de Janeiro City, Brazil

Abstract: Enteropathogens were investigated in 406 children aged 0-3 years with diarrhoea attending the Salles Neto Municipal Hospital. Enteric bacterial pathogens were isolated from 49 per cent of the children. Enterotoxigenic Escherichia coli (ETEC) (20.9 per cent), enteropathogenic E. coli (EPEC) (16.5 per cent), rotavirus (11.6 per cent), and Campylobacter (9.9 per cent) were the most common agents. Among clinical features, vomiting and fever were significantly associated with Rotavirus isolation (50.0 per cent), re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
5

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 0 publications
0
8
0
5
Order By: Relevance
“…isolated from children was slightly lower compared with the results of other authors. In Rio de Janeiro, Mangia et al (1993) found that 9.9% (15/153) of stool samples from children under 5 years of age with and without diarrhoea were positive for Campylobacter spp.…”
Section: Resultsmentioning
confidence: 99%
“…isolated from children was slightly lower compared with the results of other authors. In Rio de Janeiro, Mangia et al (1993) found that 9.9% (15/153) of stool samples from children under 5 years of age with and without diarrhoea were positive for Campylobacter spp.…”
Section: Resultsmentioning
confidence: 99%
“…They were selected on the basis of the frequency of serotypes isolated during a study previously performed in our laboratory (Regua Mangia et al 1993). For all experiments, bacteria cells were grown in brain heart infusion broth (BHI; Difco Laboratories, Detroit, Michigan, USA) for 18 hr.…”
Section: Methodsmentioning
confidence: 99%
“…Essa tendência é verificada a partir da déca-da de 80, tanto para casos graves (internados) como leves (ambulatoriais) 5,9,14 . O aumento da proporção de rotavírus entre os casos de diarréia não parece resultar de um aumento de incidência 2,3 .…”
Section: Perfil Dos Agentes Encontradosunclassified
“…Em conseqüência, nos países desenvolvidos a freqüência de quadros diarréicos por criança é de apenas 0,5 a 2 episódios por lactente/ano, enquanto que nas regiões em desenvolvimento pode atingir até mais de 10 episódios/ ano 7 . O rotavírus prepondera nos países desenvolvidos, e as bactérias são mais importantes para as crianças de países em desenvolvimento [8][9][10][11][12] .…”
Section: Introductionunclassified